1979
DOI: 10.1007/bf01315016
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice against virulent virus infection by a temperature-sensitive mutant derived from an HVJ (Sendai virus) carrier culture

Abstract: Experimental infection with HVJ (haemagglutinating virus of Japan-the Sendai strain of parainfluenza 1 virus) in mice was studied. Aerosol infection of newborn mice with the wild-type virus (HVJ-W) retarded the development of body weight and killed the animals within a few weeks. Large amounts of virus were isolated from both the lungs and the nasal turbinates of infected mice. In contrast, newborn mice exposed by inhalation to a temperature-sensitive (ts) mutant (HVJ-pB) derived from an HVJ carrier culture sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In these experiments, the viral load of SeV peaked at day 10 after infection. These results differ from the work of others [ 10 , 29 30 ], which showed that virus growth peaked in nasal turbinates, tracheas, and lungs at 5 days p.i., but may be related to difference in protocol, assessment time, and location (we did not examine turbinates or the lower airway). We found that the peak of olfactory dysfunction in the mice appeared at day 15 p.i., a time point at which the immune responses against SeV had geared up for nearly 10 days.…”
Section: Discussioncontrasting
confidence: 99%
“…In these experiments, the viral load of SeV peaked at day 10 after infection. These results differ from the work of others [ 10 , 29 30 ], which showed that virus growth peaked in nasal turbinates, tracheas, and lungs at 5 days p.i., but may be related to difference in protocol, assessment time, and location (we did not examine turbinates or the lower airway). We found that the peak of olfactory dysfunction in the mice appeared at day 15 p.i., a time point at which the immune responses against SeV had geared up for nearly 10 days.…”
Section: Discussioncontrasting
confidence: 99%
“…The primers used in this research were designed with reference to the published sequences of Sendai virus gene (Shioda et al, 1983). As reported previously (Kimura et al, 1979;Iwata et aI., 1990), virus growth peaked in nasal turbinates, tracheas, and lungs at 5 days post-infection (p.i.). Thereafter, the immune response against Sendai virus excluded progeny virus from the respiratory tracts within the subsequent 5 days.…”
Section: Parainfluenza Virus Type 1 Infects Olfactory Neurons and Estmentioning
confidence: 90%
“…There are many reports about protection of mice from Sendai virus infections by the use of killed and live vaccines. These include inactivated virus (Fukumi & Takeuchi, 1975), a synthetic oligopeptide corresponding to the partial amino acid sequence of NP protein (Kast et al, 1991), F protein-cleavage mutants (Tashiro & Homma, 1985;Itoh et al, 1990) and a temperature-sensitive mutant possessing homologous interfering capacity (Kimura et al, 1979;Kiyotani et al, 1990).…”
mentioning
confidence: 99%